Evolutionary opportunity and the limits of community similarity in replicate radiations of island lizards. (3rd October 2022) - Frishkoff, Luke Owen; Lertzman‐Lepofsky, Gavia; Mahler, D. Luke
Abstract: Ecological community structure ultimately depends on the production of community members by speciation. To understand how macroevolution shapes communities, we surveyed Anolis lizard assemblages across elevations on Jamaica and Hispaniola, neighbouring Caribbean islands similar in environment, but contrasting in the richness of their endemic evolutionary radiations. The impact of diversification on local communities depends on available spatial opportunities for speciation within or between ecologically distinct sub‐regions. In the spatially expansive lowlands of both islands, communities converge in species richness and average morphology. But communities diverge in the highlands. On Jamaica, where limited highland area restricted diversification, communities remain depauperate and consist largely of elevational generalists. In contrast, a unique fauna of high‐elevation specialists evolved in the vast Hispaniolan highlands, augmenting highland richness and driving islandwide turnover in community composition. Accounting for disparate evolutionary opportunities may illuminate when regional diversity will enhance local diversity and help predict when communities should converge in structure. Abstract : To understand how macroevolution shapes local communities, we surveyed lizard assemblages on Jamaica and Hispaniola, a pair of Caribbean islands notable for their ecological similarity, but that differ in spatial opportunities for diversification. The impact of macroevolution on local communities depends on whether environmentally‐distinct biomes are sufficiently large to support allopatric speciation and the buildup of endemic subfaunas. Where such evolutionary opportunities are plentiful (e.g., the expansive lowland forests of both islands), local controls on community structure predominate and communities converge between islands, but where they are limited (e.g., Jamaica's modest highland cloud forests), local communities bear a strong imprint of the regional species pool.